Pendampingan pemanfaatan limbah rumah tangga sebagai bahan baku pembuatan pupuk organik cair di Gampong Langkak Kabupaten Nagan Raya (Assistance for the use of household waste as a raw material for the production of liquid organic fertilizer in Langkak Village, Nagan Raya District) - Suwandi, S; Junita, Dewi; Nugroho, Yoga (Buletin Pengabdian, 2023)
Liquid organic fertilizer is made through the fermentation process of organic materials, such as animal manure, kitchen waste, or plant waste. The purpose of this community service is focused on processing household waste into raw material for making liquid organic fertilizer. The stages of the method used are socialization, discussion, and training. This activity was directly attended by 5 farmers from each farmer group in Langkak Village. This program also conveys the technical production of liquid organic fertilizer based on household waste which is explained directly through presentation techniques. The making of liquid organic fertilizer can be well-socialized in the Langkat Village community. The impact of this assistance is that the community understands and comprehends the steps for making Liquid Organic Fertilizer, and can actualize the production the utilize of Liquid Organic Fertilizer.